Benchmark Simulations of Dense Suspensions Flow Using Computational Fluid Dynamics - Haustein, M. A.; Eslami Pirharati, M.; Fataei, S.; Ivanov, D.; Jara Heredia, D.; Kijanski, N.; Lowke, D.; Mechtcherine, V.; Rostan, D.; Schäfer, T.; Schilde, C.; Steeb, H.; et al. (Frontiers in Materials, 2022)
The modeling of fresh concrete flow is still very challenging. Nevertheless, it is of highest relevance to simulate these industrially important materials with sufficient accuracy. Often, fresh concrete is assumed to show a Bingham-behavior. In numerical simulations, regularization must be used to prevent singularities. Two different regularization models, namely the a) Bi-viscous, and b) Bingham-Papanastasiou are investigated. Those models can be applied to complex flows with common simulation methods, such as the Finite Volume Method (FVM), Finite Element Method (FEM) and Smoothed Particle Hydrodynamics (SPH). Within the scope of this investigation, two common software packages from the field of FVM, namely Ansys Fluent and OpenFOAM, COMSOL Multiphysics (COMSOL) from FEM side, and HOOMD-blue.sph from the field of SPH are used to model a reference experiment and to evaluate the modeling quality. According to the results, a good agreement of data with respect to the velocity profiles for all software packages is achieved, but on the other side there are remarkable difficulties in the viscosity calculation especially in the shear- to plug-flow transition zone. Also, a minor influence of the regularization model on the velocity profile is observed.